Soft tissue sarcoma incidences and clinical characteristics are significantly different in France and Taiwan. Issue 18 (7th July 2022) - Chen, Tom Wei‐Wu; Chiang, Ruru Chun‐Ju; Le Cesne, Alex; Hsieh, Yu‐Chun; Italiano, Antoine; Yang, Ya‐Wen; Penel, Nicolas; Lee, Wen‐Chung; Bompas, Emmanuelle; Valentin, Thibaud; Anract, Philippe; Firmin, Nelly; et al.
Abstract : Background: The incidence of different soft tissue sarcoma (STS) histotypes among ethnic and geographic populations has not been comprehensively investigated. Methods: Data from 2013 to 2016 were obtained from national cancer registry databases in France and Taiwan. Liposarcoma (LPS), leiomyosarcoma (LMS), angiosarcoma (AS), synovial sarcoma (SS), and malignant peripheral nerve sheath tumor (MPNST) were selected as index STSs to estimate the age‐standardized incidence rates (ASRs) and other clinical features between patients. Results: In total, 9398 patients (7148 from France and 2250 from Taiwan) were included. The ASRs of AS (5.4 vs. 2.8) and MPNST (2.0 vs. 1.0) were significantly higher in Taiwan; France had significantly higher ASRs for LPS (12.0 vs. 10.0), LMS (9.7 vs. 7.6), and SS (1.7 vs. 1.2). Patients in Taiwan with LMS or LPS were younger than their French counterparts. With regard to the distribution according to primary anatomic site, French patients had higher odds for extremity and truncal LMS (odds ratio [OR], 2.84; p  < .001), AS (OR, 2.67; p  < .001), MPNST (OR, 1.55; p  = .027), and LPS (OR, 1.38; p  < .001) and for breast AS (OR, 10.58; p  < .001). Taiwanese patients had higher odds for liver AS (OR, 10.72; p  < .001) and uterine LMS (OR, 3.21; p  < .001). SS age and distribution according to primary anatomic site did not differ significantly between the French and Taiwanese populations. Conclusions: Significant differences in the incidence and clinical characteristics of index STS suggested that geographic (environmental) and ethnicity factors likely play a vital role in the pathogenesis of STS. Abstract : In two nationwide, population‐based cancer registry databases outside of the United States, the epidemiology of soft tissue sarcoma was investigated between Europeans and Asians. The incidence of five index soft tissue sarcoma histology subtypes differed significantly, as did the distribution according to sex, primary anatomic site, and age, between the two populations, and the results increase awareness that ethnicity and geographic factors are important in the pathogenesis of sarcoma.